Gastrointestinal Mucormycosis in a Renal Transplant Patient - Jill Tinmouth; Jeffrey Baker; Geoffrey Gardiner (Canadian Journal of Gastroenterology)
The clinical course and management of a rare case of gastrointestinal mucormycosis occurring in a renal transplant patient are presented. The diagnosis was made on pathological examination of surgically resected tissue from the colon, spleen and stomach. The patient did not survive the infection. To the best of our knowledge, this is the 11th reported case of gastrointestinal mucormycosis in a solid organ transplant patient. The pathophysiology, incidence and prognosis of this disease are discussed.